Reproductive factors and risk of melanoma. (1st August 2019) - Støer, N.C.; Botteri, E.; Ghiasvand, R.; Busund, M.; Vangen, S.; Lund, E.; Veierød, M.B.; Weiderpass, E.
Summary: Melanoma is the most severe form of skin cancer and in 2012 it accounted for 232, 000 new cancer cases and 55, 000 deaths worldwide. The most important risk factors for melanoma are exposure to ultraviolet radiation from the sun, indoor tanning, fair skin complexion, the presence of many nevi (moles) and freckles, light hair and skin reaction to sun. Female sex hormones such as estrogen and progestin have also been suggested to play a role in the development of melanoma due to the fact that melanoma is more common among females than males until the age of menopause, while the opposite is true after the age of menopause. One way to study how hormones are associated with the risk of developing melanoma is to study factors related to the female reproductive history, so called reproductive factors, such as age at menarche (first occasion of menstruation), menstrual cycle length, age at menopause and time from menarche to menopause, number of children, age at first and last birth and total breastfeeding duration. In the Norwegian Women and Cancer (NOWAC) study the authors investigated how reproductive factors were associated with the risk of melanoma overall, and by location on the body and melanoma subtype. NOWAC was initiated in 1991 and includes approximately 170, 000 women from all over the country who were followed‐up for diagnosis of melanoma until the end of 2015. During follow‐up 1, 347 melanoma cases were identified. In this large cohort the authors did not find convincing evidence of an association between reproductive factors and risk of melanoma overall. They did however observe an increased risk of the subtype superficial spreading melanoma with longer time between menarche and menopause.